Robust controller design - Dönmez, Kemal. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1985., 1985)
The aim of this thesis is to design a robust controller which solves the tracking and regulation problem and also satisfies the constraints, such as asymptotic stability, controller gain constraints, integrity, plant parameter variations, damping of the system etc. This design method guarantees that regulation and tracking occur for all perturbations of the plant, provided that the resultant system remains stable. The method of design is based on using state space approach via a two stage process: 1) Using theory, the existence of a solution and control structure to solve the problem are determined, and 2) Using nonlinear programming methods, the unkown controller parameters are determined so as to minimize a performance index for the system subject to certain constraint requirements.
Keywords: Control theory.; Mathematical optimization.